Gen Z Construction in Developing Expertise Profiles on Social Media - Devinna Anindhita Hiradan Muntaha; Windri Saifudin (Journal of Communication Studies, 2025)
The use of social media as a means of self-actualisation continues to grow, making it highly attractive for Gen Z to use as a medium for their Expertise Profiles. This research aims to explore how Gen Z utilises and constructs their personal social media to build an Expertise Profile. Gen Z uses social media, particularly Instagram and LinkedIn, simultaneously to digitally showcase their skills, achievements, and experiences. This study explores the process of virtual identity formation among Gen Z through observation and in-depth interviews with informants who actively use both platforms to meet their career needs. This research uses a qualitative descriptive approach, with data collected through interviews, observations, and literature reviews. Informants were selected using purposive sampling, and the data obtained were analysed through data reduction, data presentation, and drawing conclusions. The results of this study indicate that consistency in self-presentation and the application of cross-platform linking strategies are key to building a strong, professional image.